2019
DOI: 10.1093/neuros/nyz305
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Flow Diverter Therapy: Predictors and Management Strategies

Abstract: Flow diversion is a safe and effective treatment for many types of brain aneurysms. Even so, there remain some aneurysms that persist despite initial treatment. In studies with the longest follow-up (5 yr), at least 5% of aneurysms persist with this treatment modality. As the cumulative experience and clinical indications for flow diversion continue to expand, the anatomic and functional characteristics that are associated with aneurysm persistence are increasingly described. Identification of these factors pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
1
16
0
1
Order By: Relevance
“…FD-PASS allowed subgroup analysis of PED failure scenarios. Presence of a branch artery originating from the aneurysm sac, large/giant aneurysm size and high aspect ratio (AR) were among the most important risk factors associated with the flow diversion failure 12,25 . The FD-PASS in-silico trial replicated the effect of these morphological risk factors on aneurysm haemodynamics and occlusion (i.e., device failure).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FD-PASS allowed subgroup analysis of PED failure scenarios. Presence of a branch artery originating from the aneurysm sac, large/giant aneurysm size and high aspect ratio (AR) were among the most important risk factors associated with the flow diversion failure 12,25 . The FD-PASS in-silico trial replicated the effect of these morphological risk factors on aneurysm haemodynamics and occlusion (i.e., device failure).…”
Section: Resultsmentioning
confidence: 99%
“…Although not reported in PUFS, ASPIRe and PREMIER trials, other studies found that a branch artery emerging from the aneurysm sac [12][13][14] , fusiform aneurysm morphology 12 , bifurcation aneurysm 12 , large/giant aneurysm size 12,15 and age older than 70 years 16,17 were among the risk factors associated with incomplete aneurysm occlusion after flow diversion. The virtual FD-PASS cohort was further stratified into different subgroups to explore factors associated with FD device failure, including the presence of a branch artery arising from the aneurysm and aneurysm sac morphology.…”
mentioning
confidence: 95%
“…Although not reported in PUFS, ASPIRe, and PREMIER trials, other studies listed a branch artery emerging from the aneurysm sac [9,28,42], large/giant aneurysm size [9,11] among the risk factors associated to incomplete aneurysm occlusion after flow diversion. In-silico trials can offer detailed subgroup analysis of the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of a branch artery originating from the aneurysm sac, large/giant aneurysm size, and high aspect ratio were among the most important risk factors associated to the flow diversion failure [9,13]. The FD-PASS in-silico trial replicated the effect of these morphological risk factors on aneurysm haemodynamics and occlusion (i.e., device failure).…”
Section: In-silico Cohort Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation